Sinopsis de Scirpus s.l. (cyperaceae) para México - González Elizondo, M. Socorro; González Elizondo, Martha; Tena Flores, Jorge A.; López Enriquez, I. Lorena; Reznicek, Anton A.; Diego-Pérez, Nelly (Instituto de Ecología, A.C., 2008)
Scirpus sensu lato is a heterogeneous group from which several segregate genera have been recognized. From those, six are known from México: Scirpus sensu stricto, Amphiscirpus, Bolboschoenus, Cypringlea, Isolepis and Schoenoplectus. Two additional genera: Karinia and Oxycaryum, have been considered as a part of Scirpus but their affinity is within the tribe Cypereae. A synopsis of the group in Mexico is presented, as well as a key to the genera and their species, and data on their distribution, habitat and conservation status. Among the new records for some states are Scirpus microcarpus, previously known from Baja California and now recorded for Durango, and Schoenoplectus acutus, from northern México, which is recorded here for Michoacán.